2019
DOI: 10.1167/iovs.19-26881
|View full text |Cite
|
Sign up to set email alerts
|

The Efemp1R345W Macular Dystrophy Mutation Causes Amplified Circadian and Photophobic Responses to Light in Mice

Abstract: PurposeThe R345W mutation in EFEMP1 causes malattia leventinese, an autosomal dominant eye disease with pathogenesis similar to an early-onset age-related macular degeneration. In mice, Efemp1R345W does not cause detectable degeneration but small subretinal deposits do accumulate. The purpose of this study was to determine whether there were abnormal responses to light at this presymptomatic stage in Efemp1R345W mice.MethodsResponses to light were assessed by visual water task, circadian phase shifting, and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…7 e and f). Mutations of EFEMP1 can lead to macular dystrophy [ 37 ], and the expression of EFEMP1 was high in human and macaque foveal MGs (Fig. 7 e and f).…”
Section: Resultsmentioning
confidence: 99%
“…7 e and f). Mutations of EFEMP1 can lead to macular dystrophy [ 37 ], and the expression of EFEMP1 was high in human and macaque foveal MGs (Fig. 7 e and f).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Supplementary Table S4, ROP18 altered the expressions of 15 eye disease-related genes, including EFEMP1, SLC7A14, MIP (major intrinsic protein of lens fibe), COL25A1, CFB, SLC38A8, CFI, RIMS1, CABP4, RP1L1, CRYAB, PROM1, CRX, KCNJ13, and VCAN. Previous studies showed that EFEMP1 (Lin et al, 2018;Thompson et al, 2019), SLC7A14 (Jin et al, 2014), and RP1L1 (Albarry et al, 2019) are linked to macular degeneration or retinitis pigmentosa; COL25A1, which encodes a membrane associated collagen, is associated with oculomotor neuron development (Shinwari et al, 2015). Also, RP1L1 (Fujinami-Yokokawa et al, 2019), PROM1 Supplementary Table S2.…”
Section: Discussionmentioning
confidence: 99%
“…7ef). Mutations of EFEMP1 can lead to macular dystrophy [50], and the expression of EFEMP1 was high in human and macaque foveal MGs (Fig. 7e-f).…”
Section: Human Retinal Disease Related To Gene Expression In Retinal mentioning
confidence: 98%